The Kingdom of the Netherlands-Aruba : Technical Assistance Report-Towards a Sustainable Tax System. (IMF Staff Country Reports; Country Report, 2018)
Over the last decade, Aruba has faced three recessions resulting in a public debt of approximately 90 percent of GDP. Its current budget deficit needs to be reduced and Aruba should close a fiscal gap of 1.5-2 percent of GDP over the next two to three years to return to a sustainable path. Earlier this year, the authorities have introduced a crisis package, mainly by increasing the turnover taxes. This temporary tax measure should be replaced by a tax reform that will modernize and simplify the current system. The new tax system should not only raise more revenue, but also shift the tax burden away from income and profits toward consumption. The current system is not well equipped to make these changes. In replacing the crisis levy, the Government sees an opportunity to streamline the current tax system, modernize it, and make it more sustainable for the future needs of Aruba.